Munāsabat Muḥtawá Qanāt “Arabian Fairy Tales” bi-Muḥtawá Taʿlīm al-Lughah al-ʿArabīyah lil-Aṭfāl maʿa al-Muqarrar al-Ittiṣālī bi-Marhalat al-Adná - Utami, Laila Nadya; Abu, Asyunifar Binte (Alsina : Journal of Arabic Studies, 2023)
This research aims to determine the eligibility of the video content in the “Arabian Fairy Tales” channel with the Arabic language teaching content and the communication course at the lower level. The method used is documentation. The data source used in this research was obtained from the Arabian Fairy Tales channel. The analytical methods used are data reduction, data presentation, and conclusion. The results of this research are that in terms of categorizing the topics in the “Arabian Fairy Tales” channel, there are 45 videos that can be used as teaching materials for learning the Arabic language using the communication approach at a lower level, such as personal identity, home and family, and education.  The videos in the previously analyzed Arabian Fairy Tales channel are appropriate in terms of content, presentation, language, and imagery to the standards established by the National Education Standards Agency (BSNP) in terms of content, presentation, language, and image.